Profile of complaints of LGBTphobia occurred in health establishments in 2021: Profile of complaints of LGBTphobia occurred in health establishments in 2021 - Sousa, Rafael Gomes; Godinho Gomes, Bruna Katerine; Pereira, Luciana Barbosa; Vogt, Sibylle Emilie; Dias, Cristiano Leonardo de Oliveira; Versiani , Clara de Cássia; Dias, Orlene Veloso; Silva, Charles Caldas; Lopes, Kahena Giullia de Deus; Soares, Annie Victória Souza (Revista Unimontes Científica, 2023)
Objective: To know the profile of LGBTphobia complaints that occurred in health establishments in 2021. Methods: A descriptive, non-probabilistic quantitative approach study was carried out, with a cross-sectional cut and statistical analysis of data obtained from the Human Rights Disk. Results: There were 11,388 reports of violations suffered by the LGBT population in 2021. Of this total, 152 occurred in health facilities, in 55 of the cases the relationship between victim/suspect was user/employee, 14 of which were nurses and 13 were doctors. The male gender was the one that suffered the most LGBTphobia - 91 (60%), while the sexual orientation was homosexual - 23. The racial self-declaration of the victims prevails the brown (74). Final considerations: There is a greater number of cases of LGBTphobia involving gay men and self-reporting blacks. Divergent sexuality, combined with structural racism, makes black LGBT people even more vulnerable. There is an urgent need for health professionals to know the public policies of this population, in order to consolidate initiatives that already exist in the country.